Konsep Hukum Islam Dalam Kerjasama Bagi Hasil Pemeliharaan Hewan Kambing - Nur Wahid (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2019)
In this case the researcher used the field study method. The technique of collecting data uses documentation studies, observations, interviews, and personal experiences. The data analysis technique is descriptive qualitative, the method used to provide a description of the research subject based on data from variables obtained from the group of subjects studied and not intended to test hypotheses, the author will focus on the contract for the maintenance of goats in Argosari Village, Ayah Subdistrict Kebumen Regency. Profit sharing or profit sharing for defaults made by goat owners is illegal. If the mudarib does not get the benefit or the child of the goat, then he is entitled to receive a general wage. Therefore the owner of the capital has employed him for a certain amount of time, so he has to pay his wages, namely, get a change in the form of money that is in accordance with the price of the goat. This is based on an agreed ratio, which must be expressed as a percentage (%), not in a certain nominal value. Because if it is determined by a nominal value, it means that Shahib al-mal has set a certain profit from a business that has no clear disadvantages.